Morrer dignamente: aspectos filosóficos, jurídicos e morais da autonomia para morrer - Aubert, Anna Caramuru Pessoa (2019)
In light of the significant scientific and technological development that took place on the second half of the twentieth century, life expectancy grew considerably and, in addition to the undeniable benefits brought by medicine to people's health, it is essential to debate the new bioethical issues that arise with this advance, which made it possible for terminally ill patients with incurable diseases to outlive their natural deaths artificially and for indefinite time. In this context it becomes more and more often that the patients choose to die instead of living in a manner they don’t find dignified, and so they start to refuse treatment and ask others to help them die. Through mainly national and foreign bibliographic research and critical analysis of the legal doctrine, official sources of legislation, documents, practical cases, court decisions, and other reliable sources, the purpose of this dissertation is to verify which fundamental rights should prevail on the debate regarding the existence of a right to die, the legality of the many ways of exercising this right in the Brazilian legal framework, get in touch with other countries’ political decisions regarding such practices, debate the hard questions that arise from a legal, philosophical and moral point of view and try to dismiss the most frequently used arguments by those who oppose the existence of a right to die. In the first chapter we’ll establish the meaning of the different expressions related to the right to die, such as the many types of euthanasia, assisted suicide, dysthanasia (or therapeutic obstinacy), palliative care, and the advance healthcare directives. In the second chapter, we’ll discuss the fundamental rights envolved in the right to die debate. In the third chapter, we’ll analyze how the Brazilian legal system deals with the many forms of exercising the right to die and, afterwards, how the legal sytems of other countries do so. In the last chapter, taking into account all the information acquired in the previous chapters, we’ll seek to solve the hard questions that arise from analysing practical cases, and at the end we’ll seek to dismiss the most frequently used arguments by those who oppose the existence of a right to die